Analyzing the Causes and Solutions for Racial Disparities in Juvenile Justice Systems - Anggi Putra (Mahogany Journal De Social, 2024)
This quantitative research looks at the reasons and steps to fixing the racial inequity in the juvenile justice system and the roles played by the socioeconomic status, implicit bias, and school disciplinary measures. With the help of the in-depth processing of juvenile justice files, disciplinary records in schools, and socioeconomic indicators, and complemented by the surveys of interested parties, the study finds meaningful patterns and causal links. The results demonstrate that in poorer neighborhoods, there is a higher rate of arrest and detention, whereas more implicit bias and here severity of school disciplinary measures affect minority youth in disproportional numbers. These findings support the idea of multidimensional intervention, such as economic support of fewer privileged communities, the education of the law enforcement and school officials on implicit bias, as well as the application of restorative justice in schools. Strong empirical evidence given by this study contributes to the further research on the topic of racial inequality in the juvenile justice and indicates viable measures available to reinforce the ideas of equity and justice.